Tote bag / Balqis Nabila Ibrahim … [et al.]. - Ibrahim, Balqis Nabila; Hamzah, Muhamad Amirul Hakimi; Zamri, Nur Farhana; Nordin, Nurul Ain; Zafri, Siti Nurdamia Suria Zafira (2024)
For the ENT300 group assignment, Business Plan, our group discussed plans and the type of business to operate in Bandar Baru Bangi. Finally, we reached an agreement and decided to create a printed design tote bag called Tote Bliss. Our group's business activities were based in Bandar Baru Bangi, Selangor. Our target clients include both locals of Bandar Baru Bangi and visitors from other areas. Our group comprises five members which are Balqis, Ain, Farhana, Damia, and Amirul. Our goal is to produce elegant and flexible tote bag designs that appeal to a variety of interests. Not only that, but our major purpose is to sell high-quality tote bags that will leave our consumers satisfied. Lalaflorisa sells tote bags that are suitable for individuals of all ages, since our simplistic design makes them usable by anybody. Our tote bag design includes seven simple and appealing patterns. All designs are offered at only RM25. Tote Bliss also develops its market through social media platforms such as Instagram, X, and TikTok. Our primary goal in marketing Tote Bliss on social media is to capitalize on the potential to engage with prominent influencers in order to attract more customers from outside of Bandar Baru Bangi. We interact with consumers through Live sessions, as well as comments posted by customers or anybody else interested in our tote bags. We can learn about our company's strengths and limitations, as well as those of our competitors, by reviewing this Business Plan. As a result, we may enhance our business's flaws in order to outperform competitors. Not only that, but using this Business Plan, we may plan to obtain finances from outside parties to raise capital, as well as gain the trust of outside parties to collaborate with our company. Finally, Tote Bliss provides clients with a lovely tote bag that can be utilized by people of all ages, young and old. Not only could we buy this tote bag for ourselves, but we could also give it to others to demonstrate how much we value them. Our organization aims to reach our target revenue and deliver unforgettable gifts to our clients by exploiting our strengths and shortcomings, as well as the chances and challenges that lie ahead.